Analysis of Water Quality In Sebangau River Kereng Bengkiray Port Based On Phytoplanktons Diversity and Composition - Ridha Nirmalasari (Universitas Hasanuddin, 2018)
This research is aimed to know the diversity, composition and structure of phytoplankton community and the contamination status of organic wastes in the Sebangau river bengkiray Palangkaraya port. This research uses purposive sampling that is calculation of dominance index calculation data for phytoplankton using Simpson dominance index formula. With a total composition for all types of 756 species. The results showed that the highest composition was Bacillaria group (79%), while the other group was Chlrophyta (9%) and Cyanophytacomposition (12%). The presence of phytoplankton as an indicator that the water in the waters of the Sebangau river is not polluted, because the phytoplankton is a plant whose respiration system utilizes carbon dioxide and releases oxygen so that the water in the waters of the Sebangau River is of good quality and feasible to consumed.